"Nano Necklace" Formed by Electroless Deposition of Metal on Polymer Nanofiber for Flexible Transparent Conducting Films. (17th July 2015) - Shiratori, Seimei; Takenaka, Issei; Kyung, Kyuhong; Bernasconi, Roberto; Testa, Andrea; Magagnin, Luca
Abstract : Flexible transparent thin films are strongly required for electronic devices, display or electric equipment. To obtain both transparency and flexibility, electroless deposition on the polymer nanofiber was carried out. As the result, we successfully obtained uniformly metalized nanofiber with 300nm in diameter by all wet process without using any vacuum process.